URGENSI BIMBINGAN DAN KONSELING ISLAM BAGI LANJUT USIA - Asniti Karni (Institut Agama Islam Negeri Bengkulu, 2017)
Elderly can be said as golden age because not everyone can reach old age, so if someone has old age will require more nursing actions, both promotive and preventive, so that he can enjoy the golden age, as well as a useful old age and happy. On the contrary of old age if there is no intensive care of his family then he can not enjoy his golden age with happy. While the elderly are individuals aged 60-65 years old and above, meaning individuals who have the ability to live and sensitivity individually weak, both weak to the physical condition and weak to adjust to the environment. The existing conditions in the elderly tend to potentially cause physical health problems and mental health. Therefore it is necessary guidance and counseling Islam in order to help alleviate the problems it faces. So that the elderly in their daily lives become effective and can think that he is still useful and needed others and has the potential to stick to Islamic values.